Internal Validation of the Sepsis in Obstetrics Score to Identify Risk of Morbidity From Sepsis in Pregnancy. Issue 1 (March 2018) - Albright, C.M.; Has, P.; Rouse, D.J.; Hughes, B.L.
Abstract : ( Obstet Gynecol . 2017;130(4):747–755) Three scoring systems exist to help identify patients at risk for clinical deterioration following a diagnosis of sepsis. However, these scoring systems exclude pregnant women in their study populations. Therefore, the authors of this study developed a pregnancy-specific sepsis scoring system (Sepsis in Obstetrics Score), which accounts for the physiological changes of pregnancy.